1995
DOI: 10.1111/j.1651-2227.1995.tb13653.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping position and sudden infant death syndrome (SIDS): effect of an intervention programme to avoid prone sleeping

Abstract: The proportion of prone sleeping among sudden infant death syndrome (SIDS) victims and infants in general, and the rate of SIDS were prospectively studied in the county of Hordaland, Norway, three years before (1987-89) and three years after (1990-92) a campaign to discourage prone sleeping. Before the campaign, 64% of random reference infants were put prone versus 8% after (p < 0.0001). Concurrently, the rate of SIDS decreased from 3.5 to 1.6 per 1000 live births (63 infants before and 30 after the campaign, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 17 publications
3
66
1
1
Order By: Relevance
“…Soft bedding increases the potential of rebreathing, [1][2][3][4][5][6] a pathway through which SIDS may occur. 7 Pillows, quilts, comforters, and other soft objects are hazardous when placed under the infant [8][9][10][11][12][13][14][15] or loose in the infant's sleep area, 10,12,[15][16][17][18][19][20] increasing SIDS risk up to 5-fold, 13,15 and up to 21-fold when the infant is placed prone. 15 However, use of soft bedding and surfaces is common.…”
mentioning
confidence: 99%
“…Soft bedding increases the potential of rebreathing, [1][2][3][4][5][6] a pathway through which SIDS may occur. 7 Pillows, quilts, comforters, and other soft objects are hazardous when placed under the infant [8][9][10][11][12][13][14][15] or loose in the infant's sleep area, 10,12,[15][16][17][18][19][20] increasing SIDS risk up to 5-fold, 13,15 and up to 21-fold when the infant is placed prone. 15 However, use of soft bedding and surfaces is common.…”
mentioning
confidence: 99%
“…The supine sleeping position is recommended for infants in all western countries due to the increased risk of cot death among infants sleeping prone (e.g. AAP 2000 ;Beal 2000;Dwyer 1996;Esmail et al 1995;Fleming et al 1990;Gibson et al 2000;Markestad et al 1995;Scragg, et al 1996;Willinger et al 2000). Although recommended in the US until recently, the lateral sleep position has been discouraged for UK infants for around a decade, as several case-control SIDS studies have indicated that sleeping on the side is associated with a greater risk of SIDS than supine sleep (Fleming et al 2000;Scragg and Mitchell 1998;Skadberg et al 1998;Wigfeld et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to a change in body position or movements during sleep, infants may happen to slip under the bedding, 13,14,37,38 and a situation for CO 2 rebreathing and risk of overheating may occur. 10,13,19 Although most infants in the present study woke up when covered, there was a striking difference in subsequent behavior depending on the infants' body position.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that infants sleeping on the side may be able to pull the cover over the head, 13 and that they may roll from the unstable side position to prone. 13,14,37,38 The inability to remove the cover while prone and subsequent awakening and struggling may increase the likelihood of overheating, exhaustion, and a face down position with CO 2 rebreathing, all possible contributors to SIDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation